Ion structures and populations inside microporous carbon electrodes of electrical double-layer capacitors - Wei, Jiaqi (Nanyang Technological University, 2021)
Electrical double-layer capacitor (EDLC) is one of the most important energy storage devices famous for its high power density and long cycle life but suffers from low energy density. To expand the energy density, microporous carbons with high specific surface area and tailored porosity below 2 nm have been developed. In addition to the high specific capacitance, carbon micropores also bring distinct charging mechanisms from electrical double-layer model due to their small pore sizes. To study the working principles of microporous carbon EDLC, various experimental and theoretical approaches based on nuclear magnetic resonance, molecular dynamics, etc. have been developed in the past decade. Molecular insights such as ion desolvation and breaking of the Coulombic ordering have been revealed inside carbon micropores. Nevertheless, the ion–ion and ion–pore interactions are still poorly understood due to the lack of knowledge on ion structures and packings. New approaches are needed to address these challenges.